2020
DOI: 10.1002/cctc.202001235
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Supported Electrocatalysts Derived from Nickel‐Cobalt Modified Polyaniline Polymer for H2‐Evolution and O2‐Evolution Reactions

Abstract: The water splitting aims to produce H 2 for fuel cells and a number of industrial processes such as the ammonia synthesis and the metals refining. There is actually a major limitation about the development of cost-effective and efficient electrocatalysts to lower the cell voltage that must be overcome to perform sequentially the overall reaction that is 2H 2 O !2H 2 + O 2. In the present study, we combined Ni and Co as the promising alternative catalytic metals to Pt-group metals as well as N and S as the dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…The pristine polymer-based materials were synthesized via the chemical oxidative polymerization of aniline into polyaniline (PANI) in hydrochloric acid by ammonium persulfate. We previously showed that using ammonium persulfate as the oxidizing agent produces an emeraldine form of PANI (with polaron/bipolaron amount of 43% and base amount of 54% [ 21 ]) by using a set of physicochemical and electrochemical screenings [ 2 , 3 , 21 ]. So, the present work focuses on the polymer modified by iridium and ruthenium ( Figure 1 a) in an attempt to produce hybrid nanostructured materials with high-performance regarding HER and OER after a calcination step.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pristine polymer-based materials were synthesized via the chemical oxidative polymerization of aniline into polyaniline (PANI) in hydrochloric acid by ammonium persulfate. We previously showed that using ammonium persulfate as the oxidizing agent produces an emeraldine form of PANI (with polaron/bipolaron amount of 43% and base amount of 54% [ 21 ]) by using a set of physicochemical and electrochemical screenings [ 2 , 3 , 21 ]. So, the present work focuses on the polymer modified by iridium and ruthenium ( Figure 1 a) in an attempt to produce hybrid nanostructured materials with high-performance regarding HER and OER after a calcination step.…”
Section: Resultsmentioning
confidence: 99%
“…The different materials were synthesized by modifying our initial method [ 2 , 3 ]. Typically, 25 mL solution made of 0.5 M HCl and 0.4 M ANI was first prepared and put into a reactor at 5 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have utilized the oxidative aniline polymerization method by modifying our early process [ 41 , 42 , 43 ]. A solution S1 of 100 mL composed of 0.5 M HCl and 0.4 M ANI was prepared and kept at a controlled temperature of 5 °C.…”
Section: Experimental Methodsmentioning
confidence: 99%